Life below zero: Bank lending under negative policy rates - Florian Heider; Farzad Saidi; Glenn Schepens (European Central Bank (ECB), 2018)
We show that negative policy rates affect the supply of bank credit in a novel way. Banks are reluctant to pass on negative rates to depositors, which increases the funding cost of high-deposit banks, and reduces their net worth, relative to low-deposit banks. As a consequence, the introduction of negative policy rates by the European Central Bank in mid-2014 leads to more risk taking and less lending by euro-area banks with greater reliance on deposit funding. Our results suggest that negative rates are less accommodative, and could pose a risk to financial stability, if lending is done by high-deposit banks.
Keywords: E44; E52; E58; G20; G21; 330; negative interest rates; deposits; zero lower bound; bank balance-sheet channel; bank risk-taking channel